Role of the olivo-cerebellar complex in motor learning and control - Schweighofer, Nicolas; Lang, Eric J.; Kawato, Mitsuo (Frontiers in Neural Circuits, 2013)
How is the cerebellum capable of efficient motor learning and control despite very low firing of the inferior olive inputs, which are postulated to carry errors needed for learning and contribute to on-line motor control? Inferior olive neurons form the largest electrically coupled network in the adult human brain. Here, we discuss how intermediate coupling strengths can lead to chaotic resonance and increase information transmission of the error signal despite the very low inferior olive firing rate. This increased information transmission can then lead to more efficient learning than with weak or strong coupling. In addition, we argue that a dynamic modulation of inferior olive electrical coupling via the Purkinje cell- deep cerebellar neurons – inferior olive triangle could speed up learning and improve on-line control. Initially strong coupling would allow transmission of large errors to multiple functionally related Purkinje cells, resulting in fast but coarse learning as well as significant effects on deep cerebellar nucleus and on-line motor control. In the late phase of learning decreased coupling would allow de-synchronized IO firing, allowing high-fidelity transmission of error, resulting in slower but fine learning, and little on-line motor control effects.